Integrated genetic and epigenetic analysis of cancer‐related genes in non‐ampullary duodenal adenomas and intramucosal adenocarcinomas. Issue 3 (12th September 2020) - Ota, Ryosuke; Sawada, Takeshi; Tsuyama, Sho; Sasaki, Yasushi; Suzuki, Hiromu; Kaizaki, Yasuharu; Hasatani, Kenkei; Yamamoto, Eiichiro; Nakanishi, Hiroyoshi; Inagaki, Satoko; Tsuji, Shigetsugu; Yoshida, Naohiro; et al.
Abstract: The molecular and clinical characteristics of non‐ampullary duodenal adenomas and intramucosal adenocarcinomas are not fully understood because they are rare. To clarify these characteristics, we performed genetic and epigenetic analysis of cancer‐related genes in these lesions. One hundred and seven non‐ampullary duodenal adenomas and intramucosal adenocarcinomas, including 100 small intestinal‐type tumors (90 adenomas and 10 intramucosal adenocarcinomas) and 7 gastric‐type tumors (2 pyloric gland adenomas and 5 intramucosal adenocarcinomas), were investigated. Using bisulfite pyrosequencing, we assessed the methylation status of CpG island methylator phenotype (CIMP) markers and MLH1 . Then using next‐generation sequencing, we performed targeted exome sequence analysis within 75 cancer‐related genes in 102 lesions. There were significant differences in the clinicopathological and molecular variables between small intestinal‐ and gastric‐type tumors, which suggests the presence of at least two separate carcinogenic pathways in non‐ampullary duodenal adenocarcinomas. The prevalence of CIMP‐positive lesions was higher in intramucosal adenocarcinomas than in adenomas. Thus, concurrent hypermethylation of multiple CpG islands is likely associated with development of non‐ampullary duodenal intramucosal adenocarcinomas. Mutation analysis showed that APC was the most frequently mutated gene in these lesions (56/102; 55%), followed by KRAS (13/102; 13%), LRP1B (10/102; 10%), GNAS (8/102; 8%), ERBB3 (7/102; 7%), and RNF43 (6/102; 6%). Additionally, the high prevalence of diffuse or focal nuclear β ‐catenin accumulation (87/102; 85%) as well as mutations of WNT pathway components (60/102; 59%) indicates the importance of WNT signaling to the initiation of duodenal adenomas. The higher than previously reported frequency of APC gene mutations in small bowel adenocarcinomas as well as the difference in the APC mutation distributions between small intestinal‐type adenomas and intramucosal adenocarcinomas may indicate that the adenoma–carcinoma sequence has only limited involvement in duodenal carcinogenesis. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.